A Effort Of An Academic Supervision On Guidance And Counselling Teachers To The Success Of Students Achievements At The Junior High School Students In Jombang Regency Of East Java Indonesia (Journal of Namibian Studies : History Politics Culture, 2023)
An academic supervision is one of important tools in monitoring, controlling, and improving performance and professionalism of teachers in doing their jobs. The supervision is conducted by principals of the school. In this paper is presented the success of education in two junior high schools in Jombang Regency, East Java, Indonesia, one of them due to the supervision of principals of two school to the guidance and counselling teachers at those schools. This research is a qualitative one, in which the researcher collects data by doing observation and interview to informants, i.e., the principals and guidance and counselling teachers at both schools. Moreover, the researcher inspects all documents related to the supervision processes. The result of the research shows that a regular supervision has been conducted by the principals at least twice a year. As the results, the guidance and counselling teachers work well and show good performance in doing their job. The students’ performance is very well since they achieve many awards in many competitions in local, regional, and international levels, as well. Moreover, no serious problems in students’ bad behaviour. It can be said that the academic supervision conducted by the principals in both schools can improve the teachers and students’ performance, as well.